Low temperature impact on photosynthetic parameters of coffee genotypes - Partelli, Fábio Luiz; Vieira, Henrique Duarte; Viana, Alexandre Pio; Batista-Santos, Paula; Rodrigues, Ana Paula; Leitão, António Eduardo; Ramalho, José Cochicho (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate photoprotective mechanisms related to low positive temperatures in Coffea canephora (Conilon clones 02 and 153) and C. arabica ('Catucaí' IPR 102) genotypes, involved in cold temperature tolerance. To accomplish this, one-year-old plants were successively submitted to: temperature decrease of 0.5ºC day-1, from 25/20ºC to 13/8ºC; a three-day chilling cycle at 13/4ºC; and a recovery period of 14 days (25/20ºC). During the experiment, leaf gas exchange, chlorophyll a fluorescence and leaf photosynthetic pigment content were evaluated. Total activity of ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) and ribulose-5-phosphate kinase (Ru5PK) were quantified to measure the activity of photosynthesis key enzymes. All genotypes showed low temperature sensitivity, but displayed diverse cold impact and recovery capabilities regarding the photosynthetic-related parameters studied. Catucaí IPR 102 cultivar showed better ability to cope with cold stress than the Conilon clones, especially Conilon 02, and had full recovery of leaf gas exchange, fluorescence parameters, enzymatic activity, and higher contents of the photoprotective pigments zeaxanthin and lutein.